Pendekatan Sosiologi Hukum Dalam Memahami Konflik Agraria - Umar Sholahudin (DIMENSI - Jurnal Sosiologi, 2017)
This paper explains the approach of sociology of law to understand agrarian conflict. This legal sociology approach is used because the normative, legalistic-positivistic legal approach that has been used is not sufficiently able to explain and even provide a solution to the continuous and long-lasting agrarian conflict. Agrarian conflict, not just a matter of positive law alone, but more suabtansial it is a complex issue, related to other social issues such as law, economy and culture. The approach of legal sociology is used to understand agrarian conflicts, particularly in the land of Bongkoran Wongsorejo Banyuwangi District, to understand the issue of agrarian conflict more fully and hence can be found a way more just settlement for society.